Multilevel Analysis of the Implementation of the Health Belief Model on Antenatal Visit at Integrated Health Posts in Kapuas Hulu, West Kalimantan, Indonesia - Titis Cipta Purwanti; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Antenatal care (ANC) is carried out to prevent causes of morbidity (illness or complications) and mortality (death) in pregnant women and children. This study aimed to determine the relationship between the application of the health belief model and the behavior of utilizing/visiting antenatal services. Subjects and Method: The research was conducted with a cross-sectional study design. The approach taken was to use an analytical observational model with a sample size of 213 pregnant women. This research was conducted at the Kapuas Hulu District Health Center. This research was conducted in November-December. A sample of 213 pregnant women was selected using stratified random sampling. The dependent variable in this study is ANC visits. Meanwhile, the independent variables in this study were perceived vulnerability, perceived severity, perceived benefits, self-efficacy, and gestational age. Data collection was carried out using a questionnaire and data was analyzed using a multilevel multiple linear regression analysis model. Results: ANC visits increased with high perceived susceptibility (b= 0.13; 95% CI= 0.06 to 0.20; p < 0.001), high perceived severity (b= 0.17; 95% CI= 0.12 to 0.21; p < 0.001), high perceived benefit ( b=0.13; 95% CI= 0.09 to 0.18; p <0.001), high self-efficacy (b= 0.11; 95% CI= 0.03 to 0.18; p=0.005), and high gestational age (b= 0.15; 95% CI = 0.10 to 0.20; p < 0.001). Conclusion: Several constructs in the Health Belief Models which include perceived vulnerability, perceived severity, perceived benefits and perceived self-efficacy can be used as predictors of antenatal visits for pregnant women at Integrated service post, Kapuas Hulu Regency, West Kalimantan Province. Resulting in an ICC of 14.9%, which means there is a contextual influence of Integrated service post on antenatal visits of pregnant women.